Pakistan : 2007 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Pakistan. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Pakistan's economy continued to perform strongly owing to sound macroeconomic management and structural reform. Executive Directors advised that tight fiscal and monetary policies are required to reduce inflation and the external current account deficit while lessening pressures on real interest rates. They welcomed the enactment of the Anti-Money Laundering and Combating the Financing of Terrorism (AML/CLT) ordinance. They underscored the need to modernize the energy sector's regulatory and tariff framework and revive the privatization process. Directors urged action to strengthen public financial management.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet